Recurrent postoperative delirium in spinocerebellar ataxia type 2: a case report - Levantesi, Laura (J Med Case Rep, 2019)
BACKGROUND: Postoperative delirium is a relatively uncommon condition in middle aged patients, but very widespread in patients with psychiatric and neurological diseases undergoing general anesthesia. Few studies are currently available in the literature on the perioperative anesthesiological management of patients suffering from spinocerebellar ataxia. CASE PRESENTATION: A 58-year-old Caucasian woman affected by spinocerebellar ataxia type 2 underwent total hip arthroplasty for advanced osteoarthritis. One month later, debridement, antibiotics, and implant retention was performed for periprosthetic hip infection. Both times she underwent general anesthesia and developed an early postoperative delirium treated successfully with chlorpromazine. CONCLUSIONS: This case report highlights the need to correctly manage patients at high risk of developing postoperative delirium, especially if suffering from degenerative neurological diseases. On the other hand, further studies will be needed in order to evaluate if spinocerebellar ataxia is an independent risk factor for the development of this acute and transient pathological condition.